Occupy: A People Yet To Come - Conio, Andrew (Critical Climate Change, 2015)
The term Occupy represents a belief in the transformation of the capitalist system through a new heterogenic world of protest and activism that cannot be conceived in terms of liberal democracy, parliamentary systems, class war or vanguard politics. These conceptualisations do not articulate where power is held, nor from where transformation may issue. This collection of essays by world-leading scholars of Deleuze and Guattari examines how capitalism can be understood as a global abstract machine whose effects pervade all of life and how Occupy can be framed as a response to this as a heterogenic movement based on new tactics, revitalised democratic processes and nomadic systems of organisation. Seeing the question as a political tactic aimed at delegitimizing their protest, Occupiers refused to answer the question 'what do you want?', produce manifestos, elect leaders or act as a vanguard. Occupy: A People Yet to Come goes some considerable way towards providing the terms upon which this refusal can be understood within a changed landscape of political activism and the rewriting of the conventions of political protest. Including essays by Claire Colebrook, Giuseppina Mecchia, John Protevi, Rodrigo Nunes, Verena Andermatt Conley, Nicholas Thoburn, Ian Buchanan, David Burrows, Eugene Holland and Andrew Conio, the volume examines the economic predicates of capitalist economics: liberal democracy and its alternatives, the conjugation of protest and aesthetics, how occupy experiments with different types of leadership and how power, hierarchies and resistance might be understood using Deleuze and Guattari's radical conceptualizations of debt; subjectivity, the minor and the molecular, occupation, dispersed leadership, territory, smooth space and the war machine.